Perfil de suscetibilidade a antimicrobianos de uso clínico e a biocida clorado de bactérias isoladas de diferentes ambientes aquáticos de uma refinaria de petróleo - Luiza Camila da Silva (2020)
The concern with bacterial resistance to antimicrobials has stimulated studies on the subject beyond the hospital environment. In this work, we evaluate aquatic environments in an oil refinery, sampling from the water source intake to the cooling tower basin fed with reuse water from secondary and tertiary treatment of industrial effluents. Through cultivationdependent techniques, changes in the density of total and antimicrobial-resistant bacteria between the different sample points were analyzed, as well as the susceptibility profile of the isolates against clinical antimicrobials and chlorinated biocide. Most of the identified isolates belong to the phylum Proteobacteria, with emphasis on Pseudomonas sp. and Acinetobacter sp. Each sample showed variations between densities and population composition. Of the tested isolates, 62% showed resistance to at least one antimicrobial, highlighting the high proportion of these isolates right after secondary treatment and the reduction in subsequent steps. Approximately 45% of the isolates were not susceptible to concentrations greater than 25 mg/L of active chlorine, but we did not find a direct relationship between these values and resistance to antimicrobials. This study demonstrated that biological treatment increases resistant bacteria and although there is a decline in the amount of these bacteria after physicalchemical treatment, they are not completely removed and can still be recovered in different aquatic environments.